Agreement between international classification of disease (ICD) and cause of death and associated conditions (CODAC) for the ascertainment of cause of stillbirth (SB) in the rural areas of north India - Madhvi Kaistha; Dinesh Kumar; Ashok Bhardwaj (Wolters Kluwer Medknow Publications, 2016)
International Classification of Diseases-10 th version (ICD-10) has been used to ascertain the cause of death but its use for stillbirths (SBs) is limited. Cause of Death and Associated Conditions (CODAC) as a detailed system expected to provide the exact cause of SB, so a community-based study was planned to study the level of agreement between ICD-10 and CODAC for ascertaining the cause of SB. A verbal autopsy (VA) tool was used to collect the information and then the cause of each SB was assigned using ICD-10 and CODAC separately. Each tool was used for 87 SBs and found that prolonged singleton labor, maternal pregnancy induced hypertension (PIH), and central nervous system (CNS) related congenital malformations were considered the top three causes. There was a significant agreement between ICD-10 and CODAC but the latter offers a scope to delineate the causes more precisely due to its hierarchal nature.